The issue of land insufficiency for building mosques in urban context - Ahmad, Mohammad Firdaus; Utaberta, Nangkula; Mohd Yunus, Mohd Yazid; Ismail, Nor Atiah; Ismail, Sumarni; Mohd Ariffin, Noor Fazamimah (American-Eurasian Network for Scientific Information, 2015)
This paper presents to have a proven analysis on this current issue and will be the challenges in the future in the urban context development. For thousands of years, mosque has shaped and provided deep meaning to cities and urban communities as well as to the health, wellbeing, and quality of life for the inhabitants. For the first time in history, a majority of the world’s population is now living in urban areas. Most growth is now shaped by government bonds, tax-increment financing, and large-scale corporate returns. Despite the ascendance of economics as the touchstone for value and meaning in cities, sacred spaces are and will remain a vital part of healthy cities. Sacred spaces and gathering areas for worship have historically had a synergistic correlation with residential patterns of development. Urban areas are now experiencing tremendous growth and change, but without the diverse cultural values or faith traditions that shaped great cities of the past. Reversing this trend will be difficult in the future, with current planning and development criteria well established. Meanwhile, the issue of urbanization like of traffic movement, congestion, living cost, and social problems makes the planning and design of the urban mosque should be viewed in the perspective of sustainable living within the context of modern culture and lifestyle. In term of that, the significant and radical approach should be planned in over to solve this problem now and the future.